SETD1A Promotes Proliferation of Castration-Resistant Prostate Cancer Cells via FOXM1 Transcription - Liu Yang (Cancers, 2020)
Androgen deprivation therapy eventually leads to the development of castration-resistant prostate cancer (CRPC). Here, we demonstrate for the first time that the histone H3K4 methyltransferase SETD1A is a major regulator for the proliferation of metastatic CRPC (mCRPC). The expression of SETD1A was significantly correlated with the survival rate of patients with prostate cancer. SETD1A, which is expressed at a higher level in mCRPC than in primary prostate cancer cells, promotes the expression of FOXM1, a gene encoding a cell proliferation-specific transcription factor. SETD1A is recruited to the promoter region of FOXM1 (forkhead box M1) upon binding to E2F1, a protein that regulates the transcription of FOXM1 and contributes to the trimethylation of H3K4 in the FOXM1 promoter region. In addition, SETD1A is essential for the expression of stem cell factor (e.g., OCT4, octamer-binding transcription factor 4) and stem cell formation in mCRPC, suggesting the importance of SETD1A expression in mCRPC tumor formation. Notably, poor prognosis is associated with high expression of the SETD1A–FOXM1 pair in clinical data sets. Therefore, our study suggests that SETD1A plays an important role in the proliferation of mCRPC by regulating FOXM1 transcription.